Cardiovascular function, pulmonary gas exchange and tissue oxygenation in isoflurane-anesthetized, mechanically ventilated Beagle dogs with four levels of positive end-expiratory pressure. (May 2021) - Soares, Joao H.N.; Braun, Christina; Machado, Marcela L.; Oliveira, Renato L.; Henao-Guerrero, Natalia; Countermash-Ott, Sherryl; Allen, Irving C.; Grant, David C.; Giannella-Neto, Antonio
Abstract: Objectives: To compare pulmonary gas exchange, tissue oxygenation and cardiovascular effects of four levels of end-expiratory pressure: no positive end-expiratory pressure (ZEEP), positive end-expiratory pressure (PEEP) of maximal respiratory system compliance (PEEPmax C rs ), PEEPmax C rs  + 2 cmH2 O (PEEPmax C rs+2 ), PEEPmax C rs  + 4 cmH2 O (PEEPmax C rs+4 ), in isoflurane-anesthetized dogs. Study design: Prospective randomized crossover study. Animals: A total of seven healthy male Beagle dogs, aged 1 year and weighing 10.2 ± 0.7 kg (mean ± standard deviation). Methods: The dogs were administered acepromazine and anesthesia was induced with propofol and maintained with isoflurane. Ventilation was controlled for 4 hours with ZEEP, PEEPmax C rs, PEEPmax C rs+2 or PEEPmax C rs+4 . Cardiovascular, pulmonary gas exchange and tissue oxygenation data were evaluated at 5, 60, 120, 180 and 240 minutes of ventilation and compared using a mixed-model anova followed by Bonferroni test. p < 0.05 was considered significant. Results: Cardiac index (CI) and mean arterial pressure (MAP) were lower in all PEEP treatments at 5 minutes when compared with ZEEP. CI persisted lower throughout the 4 hours only in PEEPmax C rs+4 with the lowest CI at 5 minutes (2.15 ± 0.70 versus 3.45 ± 0.94 L minute –1 m –2 ). At 180 and 240 minutes, MAP was lower in PEEPmax C rs+4 than in PEEPmax C rs, with the lowest value at 180 minutes (58 ± 7 versus 67 ± 7 mmHg). Oxygen delivery index (DO2 I) was lower in PEEPmax C rs+4 than in ZEEP at 5, 60, 120 and 180 minutes. Venous admixture was not different among treatments. Conclusion and clinical relevance: The use of PEEP caused a transient decrease in MAP and CI in lung-healthy dogs anesthetized with isoflurane, which improved after 60 minutes of ventilation in all levels of PEEP except PEEPmax C rs+4 . A clinically significant improvement in arterial oxygenation and DO2 I was not observed with PEEPmax C rs and PEEPmax C rs+2 in comparison with ZEEP, whereas PEEPmax C rs+4 decreased DO2 I.